2008
DOI: 10.11130/jei.2008.23.4.848
|View full text |Cite
|
Sign up to set email alerts
|

The Greater Arab Free Trade Area(GAFTA): an Estimation of Its Trade Effects

Abstract: In 1997, fourteen Arab countries concluded an agreement, aimed at achieving the Greater Arab Free Trade Area (GAFTA) by 1.1.2007 at the latest. This paper provides a first ex-post appraisal of the GAFTA agreement's trade effects. Based on new theoretical developments of the gravity equation, we estimate a panel data model which covers trade within the GAFTA area as well as with 35 other reference countries, over the period 1988-2005. Several estimators are presented, especially transformed fixed-effects, Hausm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 22 publications
3
40
1
1
Order By: Relevance
“…As a result, migration can be viewed as a tool to create exports from MPs to the EU. This result is not new in the literature but it is clearly highlighted in the present study for the EU-MP relationships 9 .…”
Section: Conclusion and Policy Implicationssupporting
confidence: 59%
See 1 more Smart Citation
“…As a result, migration can be viewed as a tool to create exports from MPs to the EU. This result is not new in the literature but it is clearly highlighted in the present study for the EU-MP relationships 9 .…”
Section: Conclusion and Policy Implicationssupporting
confidence: 59%
“…It is shown that trade potential between GCC countries on the one hand and the EU and the US on the other hand is also limited [8]. It is also shown that trade potential across GAFTA countries, though significant, is also restricted, especially when the exporting country is oil producer [9]. This is mainly explained by the lack of complementarity in the trade structure of GAFTA members.…”
Section: Introductionmentioning
confidence: 83%
“…Carrere [49] concluded that "…regional trade agreements generate a significant increase in trade between members, often at the expense of the rest of the world". Abedini and Peridy [95] reported a 20% increase in trade flows between regions belonging to the GAFTA agreement. Lee and Park [59] proposed new FTAs for East Asia; they noted that trade facilitation would enhance trade creation between FTA members and reduces trade diversion among them.…”
Section: Free Trade Agreementsmentioning
confidence: 99%
“…Al Atrash and Yousef (2000) concluded that intra-Arab trade is lower than predicted by the gravity equation. Abedini and Péridy (2008) examined the impact of the Greater Arab Free Trade Area (GAFTA) and found that regional trade has increased by 20% since GAFTA was implemented. Boughanmi (2008), focusing on the Gulf region, showed that in spite of the fact that the share of GCC intra-trade is too small in absolute terms, it is actually higher than expected on the basis of underlying trade determinants.…”
Section: A Intra-arab Integration and Fdi Inflowsmentioning
confidence: 99%